A series of metal–organic frameworks constructed by a rigid-flexible 5-(bis(4-carboxybenzyl)amino)isophthalic acid: syntheses, crystal structures and physical properties. Issue 48 (21st November 2018) - Qiao, Yu; Ma, Yufeng; Jiang, Wei; Wang, Xiuyan; Guan, Weisheng; Che, Guangbo; Li, Weikang; Qin, Fang
Abstract : Four new MOFs have been hydrothermally synthesized and characterized. Abstract : Four new metal–organic frameworks (MOFs), namely, [Zn2 L] n (1 ), [Mn(H2 L)(H2 O)] n (2 ), [Cd(H2 L)(H2 O)2 ] n · n H2 O (3 ) and [Pb2 L(H2 O)] n ·3 n H2 O· n DMF (4 ), have been prepared by using a tetracarboxylic acid ligand H4 L (H4 L = 5-(bis(4-carboxybenzyl)amino)isophthalic acid) under hydrothermal conditions and structurally characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction analysis and powder X-ray diffraction. Structural analyses revealed that1, 2 and4 exhibit three-dimensional network structures. The structure of1 can be symbolized as a 2-nodal 6-connected net with a (4 11 ·6 4 )(4 7 ·6 8 ) topology. The framework of2 can be considered as a 4-connected net with a (6 2 ·8 4 )(6 3 ·8 3 ) topology. The structure of4 can be regarded as a 5-connected net with a 4 3 ·6 6 ·8 topology. In contrast, 3 exhibits a 2D structure with a 3, 3-connencted (6 3 )2 topology. These MOFs exhibit excellent photocatalytic activities for dye degradation under visible light irradiation. Furthermore, 2 displays weak antiferromagnetic interaction at low temperature.